2017
DOI: 10.1007/s10068-017-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of shelf-life and changes in the quality characteristics of semidried persimmons stored at different temperatures

Abstract: his study was performed to investigate changes in the quality characteristics and shelf-life of semidried persimmons stored at different temperatures using acceleration experiments. In order to estimate quality changes in the samples, we evaluated the physicochemical properties, microbiological changes, and sensory features of the samples periodically after storage at -20, -10, 0, and 10 °C. At all storage temperatures, CIE values decreased significantly. Based on the results of this study, regression equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…is is probably due to different process conditions such as drying method. Dried persimmons are usually dried by sun drying, and thus, major problems regarding color change, mold growth, and other damages occur during the drying process [5]. Dried persimmon-1 and dried persimmon-2 used in this study were manufactured by vacuum drying and hotcool air drying, respectively.…”
Section: Microbial Populations In Dried Persimmons At Differentmentioning
confidence: 99%
See 2 more Smart Citations
“…is is probably due to different process conditions such as drying method. Dried persimmons are usually dried by sun drying, and thus, major problems regarding color change, mold growth, and other damages occur during the drying process [5]. Dried persimmon-1 and dried persimmon-2 used in this study were manufactured by vacuum drying and hotcool air drying, respectively.…”
Section: Microbial Populations In Dried Persimmons At Differentmentioning
confidence: 99%
“…In other words, storage temperature of dried foods is important to prevent color changes during storage. Choi et al [5] observed that the L * , a * , and b * values were significantly decreased in semidried persimmons during storage for 20, 25, and 80 days at 10, 0, and − 10°C, respectively. Cárcel et al [14] also reported that the color change in dried persimmons was reduced at 2°C (ΔL * − 12.0%) than at 28°C (ΔL * − 46.4%) after storage for 409 days.…”
Section: Microbial Populations In Dried Persimmons At Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an oxygen scavenger, moisture content of the dried persimmon, and packaging material that is used have also been shown to affect quality changes during the storage period (Hayashi, 1990). For instance, Choi et al (2017) mentioned that semi-dried persimmons that are stored under freezing conditions may expire within 6 months when packaged in normal paper boxes but the shelf life increases to 1 year when stored in modified atmosphere packaging. However, few studies have investigated the quality changes that occur in dried persimmon during storage and transportation, highlighting the need for further research in this field.…”
Section: Hyun Et Al 2019mentioning
confidence: 99%
“…It is difficult for manufacturers to a Received 18 July 2018/Accepted 24 August 2018 establish an accurate use by date due to practical limitations such as the marketplace complexities (15). Often, tests such as Accelerated Shelf-Life tests (ASLTs) are used to identify shelf life by selecting and analysing kinetic elements which are responsible for contamination as well as calculate what the shelf life might be in storage conditions (16). Spoilage refers to microbiological changes as well as the presence of clouds, discoloration, presence of particulates and gas buildup (13,17).…”
Section: Changes Of Microbial Load In Packet Orange Juice After Expirmentioning
confidence: 99%